1993
DOI: 10.1161/01.str.24.8.1241
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin levels in subarachnoid clot and effects on canine arterial smooth muscle cells.

Abstract: Previous studies have suggested that bilirubin is a potential contributor to cerebral vasospasm. The purpose of this investigation was to determine whether bilirubin accrues in subarachnoid clot, whether its vasoconstrictive effect could involve a direct action on arterial smooth muscle cells, and, if so, whether bilirubin affects their Ca2+ uptake. Subarachnoid clots were analyzed for bilirubin using high-performance liquid chromatography. The length and 45Ca2+ uptake of vascular smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…It is relatively well known that the spinal fluid of the subarachnoid haemorrhage patients was vasoactive and cytotoxic [2,10,37], but only recently were the BOXes reported in the haemorrhage patients' spinal fluid [38]. Interestingly, increased bilirubin in the spinal fluid of the subarachnoid haemorrhage patient has a time course that is similar to the reported incidence of vasospasm [8,47].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is relatively well known that the spinal fluid of the subarachnoid haemorrhage patients was vasoactive and cytotoxic [2,10,37], but only recently were the BOXes reported in the haemorrhage patients' spinal fluid [38]. Interestingly, increased bilirubin in the spinal fluid of the subarachnoid haemorrhage patient has a time course that is similar to the reported incidence of vasospasm [8,47].…”
Section: Discussionmentioning
confidence: 73%
“…Bilirubin levels rise in the spinal fluid following subarachnoid haemorrhage [31] and their time course correlates well with the accepted time course of cerebral vasospasm, but bilirubin is not vasoactive. Thus there has been an interest in bilirubin's association with vasospasm, though with mixed results [3,4,8,9,27,28,30,32,38,47]. A bilirubin derivative such as BOXes is therefore quite consistent with the clinical characteristics of vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2ϩ -binding properties of bilirubin itself (11) provide extra-and intracellular Ca 2ϩ sinks, while the reduced expression of parvalbumin reported in Gunn rats (albeit for neuronal tissue) (28) could limit contractility if arising in the myocardium. On the other hand, bilirubin can increase smooth muscle permeability to Ca 2ϩ (32). Antioxidant actions of bilirubin might also modify redox-dependent control of contraction (31), whereas Malik et al (17) have shown that bilirubin negatively influences mitochondrial energy production, thus potentially energy-dependent contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its antioxidant activity BR can serve as a protective agent in cells, membrane lipids and low‐density lipoproteins (LDL) exposed to oxidative stress [5–8]. High levels of BR are found in clots in the perivascular area and in CSF following SAH (CSF SAH ; cerebrospinal fluid from subarachnoid haemorrhage patients) [9,10].…”
mentioning
confidence: 99%
“…There have been extensive studies searching for the vasoactive compounds in the CSF of SAH patients [1–6,9–11,14]. Bilirubin had been implicated but never shown to be the cause of cerebral vasospasm.…”
mentioning
confidence: 99%